Preserving inferior right hepatic vein enabled bisegmentectomy 7 and 8 without venous congestion: a case report - Masayoshi Terayama; Kyoji Ito; Nobuyuki Takemura; Fuyuki Inagaki; Fuminori Mihara; Norihiro Kokudo (Surgical Case Reports)
Abstract Background In hepatectomy, the preservation of portal perfusion and venous drainage in the remnant liver is important for securing postoperative hepatic function. Right hepatectomy is generally indicated when a hepatic tumor involves the right hepatic vein (RHV). However, if a sizable inferior RHV (IRHV) exists, hepatectomy with preservation of the IRHV territory may be another option. In this case, we verified the clinical feasibility of anatomical bisegmentectomy 7 and 8 with RHV ligation, averting the right hepatic parenchyma from venous congestion, utilizing the presence of the IRHV. Case presentation A 70-year-old man was presented with a large hepatic tumor infiltrating the RHV on computed tomography during a medical checkup. The patient was diagnosed with hepatocellular carcinoma (HCC), T2N0M0, stage III. Right hepatectomy was first considered, but multi-detector computed tomography (MDCT) also revealed a large IRHV draining almost all of segments 5 and 6, suggesting that IRHV-preserving liver resection may be another option. The calculated future remnant liver volumes were 382 mL (26.1% of the total volume) after right hepatectomy and 755 mL (51.7% of the total volume) after anatomical bisegmentectomy 7 and 8; therefore, we scheduled IRHV-preserving anatomical bisegmentectomy 7 and 8 considering the prevention of postoperative liver failure and increased chance of performing repeat resections in cases of recurrence. Preoperative three-dimensional simulation using MDCT clearly revealed the portal perfusion area and venous drainage territories by the RHV and IRHV. There was an issue with invisibility of the anatomical resection line of segments 7 and 8, which was completely dissolved by intraoperative ultrasonography using Sonazoid and the portal dye injection technique with counter staining. The postoperative course in the patient was uneventful, without recurrence of HCC, for 30 months after hepatectomy. Conclusions IRHV-preserving anatomical bisegmentectomy 7 and 8 is a safe and feasible procedure utilizing the three-dimensional simulation of the portal perfusion area and venous drainage territories and the portal dye injection technique.